Lost (and Found) in Translation: The Reception of Pinel’s and Esquirol’s Psychiatric Theories and the Conformation of Melancholy, Hypochondria, Mania and Hysteria in Spain, 1800–1855 (Theatrum historiae, 2021)
In the history of psychiatry in Spain, the first half of the nineteenth century has been considered a period of uncritical reception of the theories of Philippe Pinel and Jean Étienne Esquirol. In this article I strive to problematise the diffusionist assumptions of this thesis, studying the participation of local agents in the circulation and reception of medical knowledge. Through a comparative analysis of the paratexts and the modifications made to the translations of the works of these authors, I intend to expose how the theories of Pinel and Esquirol were unified in the Spanish case. Through a concrete analysis of the modification of the diagnoses of melancholy, hypochondria, mania and hysteria, I intend to expose the variations that were applied to medical knowledge in its reception in Spain in order to adapt it to the frameworks of local medicine. Lastly, I intend to expose the methodological advantages offered by conceiving the translations of works and books as cultural products whose meaning is constructed in its place of rception, and not in the place of original publication.
Keywords: History of Psychiatry; Circulation of Knowledge; 19thCentury; Spain; Hysteria